Biomarkers in Neurodegenerative Diseases - Ghosh, Arnab (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the recent advancements in both fundamental and clinical research, focusing on identifying, developing, and applying new and improved biological markers for specific neurologic disorders in the future. The original research work and review articles published here highlight some unique mechanisms underlying the most prevalent pathophysiological conditions affecting human health. Other areas covered in the book include emerging treatment options and correct diagnoses using different biochemical and imaging techniques.